Réponses

2013-05-10T00:49:01+02:00

a.

( x + 1)² = -1

x² + 2x +1 = -1

x² + 2x + 2 = 0

 

DELTA = b² - 4ac = 2² - 4 * 1 * 2 = -4

DELTA < 0 donc pas de solutions

 

 b.

(4x - 8)² = ( 3x + 1)²

16x² - 64x + 64 = 9x² + 6x +1

7x² - 70x + 63 = 0

x² - 10x +9 = 0

 

DELTA =  100 - 36 = 64

DELTA > 0 donc 2 solutions.

 

Soit x = ( b² - RACINE(DELTA) ) / 2a     soit  x = ( b² + RACINE(DELTA) ) / 2a

Donc x = (100 - 8) / 2 = 46   ou x = ( 100 + 8) / 2 = 54

 

 

c.

4x² + 4x + 1 = 121

4x² + 4x - 120 = 0

x² + x - 30 = 0

 

DELTA = 1 - 4 * (-30) = 121

DELTA > 0 donc deux solutions

x = ( 1 - 11) / 2 = -5   ou x =( 1 +11) / 2 = 6